Analisis postur kerja dan redesain fasilitas bagian pengemasan (studi kasus pada PT RNM) - Ida Bagus Suryaningrat; El Daffa Ramadiansyah; Ragil Ismi; Andrew Setiawan Rusdianto; Noer Novijanto (AGROINTEK, 2025)
One of the subsidiaries of PT Perkebunan Nusantara XII is PT Rolas Nusantara Mandiri (PT RNM). This company is a producer of quality coffee products and was established in 2007, which in terms of experience in processing and managing coffee sales systems is beyond doubt. Packaging workers in the UKB PT RNM complained about the lack of comfortable work facilities and also pain in certain parts of the body. The purposes of this research are to analyze the work posture of packaging workers at UKB PT RNM, analyze the risk level of complaints of musculoskeletal disorders (MSDs) at UKB PT RNM, and design packaging station work facilities according to anthropometric data processing and QFD methods. The data processing stages in this research include processing NBM worksheet data, REBA, then processing QFD data, then processing anthropometric data, and work facility dimensions. The anthropometric data was first tested for data adequacy and uniformity and then redesigned the work facility design with new design dimensions. The results of this research include the results of the NBM, complaints of moderate pain were 77.97%, complaints of pain were 6.78%, and complaints of very pain were 15.25%. Dominant complaints of pain in the neck, wrists, fingers, back, waist, buttocks and thighs. Then the REBA results showed that the three packages of Mount Ijen coffee were included in the very high-risk level category. Work facility design redesign was carried out on work chairs and sliders. Chairs are made to have soft seat backs and cushions and sliders are more practical.